GAME MODEL IN THE GEOSTRATEGIC RIVALRY OF GREECE AND TURKEY - Vignjević, Marko (Political Review, 2024)
The paper analyzes the geostrategic rivalry between Greece and Turkey in the Aegean Sea and the Eastern Mediterranean with the help of game theory. From the scientific aspect, the goal is to expand the game theory in political science, more precisely in the interstate relations that share certain elements with the game model (competition, strategic interactions and conflicts). The issue of Greek-Turkish rivalry is important for extensive regional security, and for Serbia's foreign policy, given the importance of its bilateral relations with these countries. The structure of the paper consists of two parts. In the first part, the use of game theory in the analysis of foreign and security policy is discussed, not only the scientific domain of the theory is apostrophized, but also the possibilities of its practical application at the level of the state apparatus that deals with this type of analysis. The second part of the paper indicates the key segments of the geostrategic interest of Turkey and Greece in the waters of the Aegean Sea and the Eastern Mediterranean, as well as the security-risky collision of those interests. Game theory, specifically the “persuasion game” with its “focal points”, could assess whether tensions between two states will escalate into direct armed conflict or whether the rivals will eventually be cooperative. When examining the model of the “persuasion game” in the Greek-Turkish rivalry, “focal points” were determined and divided into those that directly result from the political dialogue between Athens and Ankara and those that are influenced by the regional political-security constellation.
Keywords: Greece; Turkey; game theory; persuasion game; foreign policy; security; geostrategy; Aegean Sea; Eastern Mediterranean